The role of person-organisation fit in attraction and selection decisions - Billsberry, Jon (2003)
Schneider's Attraction-Selection-Attrition cycle (ASA; Schneider, 1987) is one of the most influential models in the person-organisation (P-0) fit literature. The main idea in this framework is that organisations attract, select, and retain those people who share their values. Schneider (1987) argues that this cycle creates homogeneity in the type of people employed by the organisation. He predicts that over time this homogeneity is dysfunctional for organisations as they become increasingly ingrown and resistant to change.